Answer: 4 years
Step-by-step explanation:
144 + 8(4) = 176
108 - 5(4) = 88
88 x 2 = 176
Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
where are the options am not seeing them
Answer:
3/2
Step-by-step explanation:
Given the equation 3/2(4x-2)-3x = 5-(x+2)
Open the parenthesis
3/2(4x) - 3/2(2) -3x = 5-x-2
6x-3-3x = 3-x
3x-3 = 3-x
Collect like terms
3x+x = 3+3
4x = 6
Divide both sides by
4x/4 = 6/4
x = 3/2
Hence the value of x is 3/2